Protoplasmaströmung - Nitella - IWF (IWF (Göttingen), 1980)
(en)Rotational streaming in the internode cells of Nitella flexilis (Characeae). The chloroplasts lie in the unmoved plasmatic wall surface. The inner streaming plasmatic layer moves the vacuole sap. The chloroplast free zone, the indifference layer, marks the border between back and forth streaming plasma.